Validation and practical implementation of seated position radiotherapy in a commercial TPS for proton therapy. (December 2020) - Maes, Dominic; Janson, Martin; Regmi, Rajesh; Egan, Alexander; Rosenfeld, Anatoly; Bloch, Charles; Wong, Tony; Saini, Jatinder
Highlights: Chair based treatment in seated position are very common in particle therapy centers. RaySearch has introduced new 6D couch features that could be used for chair-based treatments. These 6D couch features are validated to ensure compliance with IEC61712. A seamless workflow to implemented treatments in a seated position is presented. Abstract: Purpose: This work aims to validate new 6D couch features and their implementation for seated radiotherapy in RayStation (RS) treatment planning system (TPS). Materials and methods: In RS TPS, new 6D couch features are (i) chair support device, (ii) patient treatment option of "Sitting: face towards the front of the chair", and (iii) patient support pitch and roll capabilities. The validation of pitch and roll was performed by comparing TPS generated DRRs with planar x-rays. Dosimetric tests through measurement by 2D ion chamber array were performed for beams created with varied scanning and treatment orientation and 6D couch rotations. For the implementation of 6D couch features for treatments in a seated position, the TPS and oncology information system (Mosaiq) settings are described for a commercial chair. An end-to-end test using an anthropomorphic phantom was performed to test the complete workflow from simulation to treatment delivery. Results: The 6D couch features were found to have a consistent implementation that met IEC 61712 standard. The DRRs were found to have an acceptable agreement with planar x-rays based on visual inspection. For dose map comparison between measured and calculated, the gamma index analysis for all the beams was >95% at a 3% dose-difference and 3 mm distance-to-agreement tolerances. For an end-to end-testing, the phantom was successfully set up at isocenter in the seated position and treatment was delivered. Conclusions: Chair-based treatments in a seated position can be implemented in RayStation through the use of newly released 6D couch features.